An Edwardsiella piscicida esaS mutant reveals contribution to virulence and vaccine potential. (June 2020) - Edrees, Asmaa; Abdelhamed, Hossam; Nho, Seong-Won; Ozdemir, Ozan; Karsi, Attila; Essa, Manal; Lawrence, Mark L.
Abstract: Edwardsiella piscicida is a Gram-negative pathogen that causes disease in diverse aquatic organisms. The disease leads to extensive losses in commercial aquaculture species, including farmed U.S. catfish. The type III secretion system (T3SS) often contributes to virulence of Gram-negative bacteria. The E. piscicida esaS gene encodes a predicted T3SS export apparatus protein. In the current study, an E. piscicida esaS mutant was constructed and characterized to increase our understanding of the role of T3SS in E. piscicida virulence. Deletion of esaS did not significantly affect biofilm formation and hemolytic activity of E. piscicida, but it had significant effects on expression of hemolysis and T3SS effector genes during biofilm growth. Ep Δ esaS showed significantly (P < 0.05) reduced virulence in catfish compared to the parent strain. No mortalities occurred in fish infected with Ep Δ esaS at 6.3 × 10 5 and 1.26 × 10 6 CFU/fish compared to 26% mortality in fish infected with wild-type E. piscicida at 7.5 × 10 5 CFU/fish. Bioluminescence imaging indicated that Ep Δ esaS invades catfish and colonizes for a short period in the organs. Furthermore, catfish immunized with Ep Δ esaS at 6.3 × 10 5 and 1.26 × 10 6 CFU provided 47% and 87% relative percent survival, respectively. These findings demonstrated that esaS plays a role in E. piscicida virulence, and the deletion mutant has vaccine potential for protection against wild-type E. piscicida infection. Highlights: The esaS gene contribute to hemolysis during biofilm growth but not during planktonic growth. The esaS is needed for optimal expression of T3SS effectors during biofilm growth. A Δ esaS mutant is attenuated in catfish but still possesses the ability to invade the host tissues for a short period.